Analisis Struktur dan Komposisi Vegetasi di Daerah Tangkapan Air Danau Karu, Pulau Obi, Kabupaten Halmahera Selatan, Provinsi Maluku Utara - Nana Sudiana; Akhmadi Puguh Raharjo (Jurnal ALAMI : Jurnal Teknologi Reduksi Risiko Bencana, 2018)
Obi Island possess substantial natural resource potential in the form of nickel ore. Since 2014, exports of raw mineral resources have been banned and the government obligate the construction of smelters. The amount of energy and water needed for smelter requires careful planning in relation to the potential water resource available in proximity to smelter construction site, which in this case is Lake Karu. The purpose of this study was to determine the condition of the structure and composition of vegetation in the catchment area of Lake Karu. Data collected were diameter at breast height (dbh) and height of vegetation from each growth state (seedlings, saplings, poles and trees). Sampling method used for vegetation data collection were in the form of a plot in a transect. The measurement results obtained from field surveys were then analyzed to obtain the Important Value Index (IVI) of each type of vegetation and Shannon-Wiener diversity index. From this study it is known that there are three classes of lowland forest in the study location. When sorted from the most diverse to the most uniform, the sequence is: heterogeneous lowland forests, forests in river corridors and homogeneous lowland forests. Forest conditions in the study sites are in good condition and further research is needed to add more depth to this study.